Development of a Gymnastics Movement through Exploration of the Cultural Values of the Aceh Rampoe Dance in Langsa City - Yoki Afriandy Rangkuti; Rizkei Kurniawan; Dedi Andriansyah; Muhammad Fauzan Isma (UNIB Press, 2021)
This study is a study that explores cultural values and develops a gymnastic movement that originates from the Aceh Rampoe dance in Langsa City. The research method used is a combination of qualitative research and development (Research & Development) from Brog and Gall. In the part of exploring the cultural values of the Rampoe Aceh dance, qualitative research methods are used with a holistic approach through in-depth interviews and direct observation at dance studios. Historical analysis of this dance is not a traditional Aceh dance that has existed for a long time. accordance with the terminology of the naming